La ricerca dell’origine della lingua. Messianismo e materialismo storico nella riflessione linguistica di Benjamin. Un confronto con Platone - Disegni, Manuel (Rivista Italiana di Filosofia del Linguaggio)
his essay submits some theoretical considerations about the linguistic thought of Walter Benjamin with particular regard to his early text On Language as Such and on the Language of Man. It firstly aims to locate the problem of language into the context of Benjamin’s philosophy by clarifying its systematic place, namely by pointing out its connections to the conception of knowledge and of history. The essay avails itself of the later Benjaminian concepts of messianism and historical materialism, which appear necessary to a thorough understanding of his earlier, avant-garde writings. Furthermore Benjamin’s linguistic reflection is compared and contrasted with those of some influential sources of his, among which it has been opted for Plato, Marx and Scholem. The essay argues that Benjamin’s should not be read as a theory of language. It should be rather qualified as a critique of language or, which is the same, as a philosophy of its history, meaning an ideal interpretation of the concrete historical development of the human ability to speak. Particular attention has to be payed to the long-time question about the adamitic, the original language. By means of Benjamin’s peculiar concept of origin, it is possible to understand the turn of this question into an inquiry concerning the mythical dimension of language, meaning its asserted capacity to immediately reveal the truth. The traditional dichotomy between natural (or divine) and conventional (or social) genesis of language, unmasked as mere abstract opposition, becomes an occasion to think about the double nature of language: a means to signify the truth and at the same time the medium in which truth expresses itself. The oversight of this double character of language generates its fetishisation, that is to say the presumption that the linguistic turn in Western philosophy represents a progress away from superstition and hypostatisation towards the truth.